Indian Philosophy and Environmental Ethics - Ravikanth, Gudasala (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
The history of the human relationship with nature is based on the idea of mastery or domination. Till recently the effects of human activity upon nature were regarded as morally neutral. In recent years, humans have now realized that their interventions in nature have caused massive damage to the harmony of the ecosystem. This knowledge subsequently led humans to explore the ways through which further damage to the eco-systems can be prevented. The promotion of environmental ethics was taken into consideration, to help protect future generations from ecological threats and calamities. Environmental ethics is an important perspective because it helps in subscribing to moral values and duties that man must have towards nature. However, religion is often considered the most widely used system to make ethical decisions and conduct moral reasoning. Most world religions are eco-friendly and share a common ethic based on harmony with nature. Due to the above, this study attempts to scrutinize the contribution of the two oldest living religions within the Indian philosophical tradition to environmental ethics. The literature on both Hinduism and Jainism and the environment is vast and growing quickly. However, much of these pieces of literature fail to define key terms and make essential assumptions explicit. Consequently, in this work, I clarified central concepts (Anekāntavāda, dharma, satyāgraha, and Vasudhaiva Kutumbakam) within both religions and show how they foster environmental awareness. This paper gives an insight into the importance of the environment in Indian’s oldest religions - Hinduism and Jainism.